Vascular Effects of Aqueous Extract of Chamaemelum nobile : In Vitro Pharmacological Studies in Rats. (May 2013) - Zeggwagh, Naoufel Ali; Michel, Jean Baptiste; Eddouks, Mohamed
<x xml:space="preserve">Abstract</x> This study aims to evaluate the in vitro vasorelaxant effect of C. nobile aqueous extract. We use aortic ring isolated from Wistar rats and aqueous C. nobile extract at doses of 5, 10 and 20 mg/ml. Incubation of aqueous C. nobile extract for 30 minutes produced a significant shift of the dose–response curve to norepinephrine (NE) (10–8 to 10–5 M) (p < 0.001). This study demonstrates that aqueous C. nobile extract possesses in vitro vasorelaxant effect.